Use of a GPGPU means for the development of search programs of defects of monochrome half-tone pictures - Dudnik, V.A.; Kudryavtsev, V.I.; Sereda, T.M.; Us, S.A.; Shestakov, M.V. (Вопросы атомной науки и техники, 2013)
Application of a GPGPU means for the development of search programs of defects of monochrome half-tone pictures is described. The description of realization of algorithm of search of images' defects by the means of technology CUDA (Compute Unified Device Architecture - the unified hardware-software decision for parallel calculations on GPU) companies NVIDIA is resulted. It is done the comparison of the temporary characteristics of performance of images' updating without application GPU and with use of opportunities of graphic processor GeForce 8800.